African particularities of sudden adult death in Togo on autopsy cases - Tchin Darre (Heliyon, 2021)
Background: The purpose of the study was to determine the circumstances of occurrence of these sudden deaths, risk factors, to identify the causes of sudden death in adults at autopsy, with a view to improving prevention. Methods: This is a retrospective study of the cases of sudden death that were the subject of an autopsy in the pathology anatomy department of the University Hospital Sylvanus Olympio in Lomé from 2009 to 2018. Results: A total of 318 sudden death cases were recorded. The sex ratio (M/F) was 1.8, and the mean age was 43 ± 0.36 years. Sudden deaths were the second most common reason for autopsies after traffic accidents. The place of death was home in 76.7% of cases and in hospitals in 23.3%. Obesity was noted in 59.4%, with an umbilical adipose panicle varying between 7 and 12 cm thick. Cardiovascular causes excluding cerebral involvement (n = 173 cases, 54.40%) followed by pulmonary causes (n = 100 cases, 31.44%) were the most common cause of sudden death. The predominant cardiac pathology was infarction accounting for 32.07% of all causes of sudden death, and pulmonary embolism with 19.49% was the leading cause at the pulmonary level. Conclusion: The victims of sudden death in Togo are relatively young, predominantly male and predominantly obese. The main causes of sudden death were myocardial infarction followed by pulmonary embolism. The prevention of sudden death remains paramount, especially in the African context, where pre-hospital care is often inadequate.